Localized Delivery of Drugs through Medical Textiles for Treatment of Burns: A Perspective Approach - Ruchi Tiwari; Gaurav Tiwari; Akanksha Lahiri; Vadivelan R; Awani K Rai (Tabriz University of Medical Sciences, 2021)
The topical delivery offers numerous benefits, such as the ability to deliver drugs specifically on site selectively, prevents fluctuations in the levels of the drug, improved compliance, and improved self-medication capacity. Skin is the main route of the administration of the drug delivery system (DDS) and burns mainly cause skin damage. A burn is a kind of damage caused to skin and tissues by fire, ice, electrical energy, pollutants, friction, and radiation. There are three different types of burns, including superficial epidermis burns, partial-thickness dermis that stretch to the papillary and reticular dermis, and full-thickness burns that cover the dermis whole. The objective of the present review article is to focus on fabrication techniques of medical textiles, different types of polymers used for designing medicated textiles, skin burn conditions, and application of medicated textiles for treatment of burn along with other applications. Cream, ointment, and gel are the dosage forms used in burns. Intravenous fluids, wound care, assorted antibiotics, surgical and alternative medicines, burned creams and salami, dressings can be used to treat wounds. Nanofibers are nanometer-specific fibers that encapsulate drugs inside them and cure wounds. Nanofibers have all the properties that speed up wound healing. The properties are mechanical integrity, proper timing of wound addiction, temperature homeostasis facilitation and gas exchange, absorption of exudates. The nanofibers have been used in burn care and have been highly efficient and non-toxic.